2020
DOI: 10.1159/000512396
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Scleral Thickness in Myopic Eyes and Its Association with Ocular Parameters

Abstract: Purpose: This study was designed to determine whether the anterior scleral thickness is affected by axial elongation and to investigate the association between anterior scleral thickness and various ocular parameters in myopic eyes. Methods: This cross-sectional study included 79 healthy myopic participants. Anterior scleral thickness was measured in eight meridians (superior-nasal [SN], superior [S], superior-temporal [ST], temporal [T], inferior-temporal [IT], inferior [I], inferior-nasal [IN], and nasal [N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 24 publications
3
23
1
Order By: Relevance
“…Our outcomes demonstrate that AST variations with scleral eccentricity occurred, which were significantly only over the temporal region. Several authors [17, 18, 25-27, 38] reported that scleral thickness decreased significantly from the SS region toward the scleral equator for all meridians. However, it could be reasonable to find a small disparity considering that the present study analyzes the AST without taking into account the diversity of refractive error (emmetropes, n = 30, SE range = +0.75 to −0.75 D, mild myopes, n = 16, SE range = −1.0 to −3.0 D and moderate myopes, n = 4, SE range = −3.0 to −6.0 D).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our outcomes demonstrate that AST variations with scleral eccentricity occurred, which were significantly only over the temporal region. Several authors [17, 18, 25-27, 38] reported that scleral thickness decreased significantly from the SS region toward the scleral equator for all meridians. However, it could be reasonable to find a small disparity considering that the present study analyzes the AST without taking into account the diversity of refractive error (emmetropes, n = 30, SE range = +0.75 to −0.75 D, mild myopes, n = 16, SE range = −1.0 to −3.0 D and moderate myopes, n = 4, SE range = −3.0 to −6.0 D).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that gender and age were not factors associated with AST. However, controversial results can be found about their relationship with AST in the literature [18, 21, 25-27, 38, 44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, it has limited capability to expand whether we need more cells injected (Sharma et al, 1997). Whereas we did not use retrobulbar injection because it does not contribute in sclera-retina signaling loop and also potentially obstruct lymph circulation (Siegwart et al, 2002;Smith et al, 2009, Sung et al, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the topographic difference of the anterior sclera thickness according to the axial elongation that have shown various correlations, and the distribution of sclera thickness has also varied in previous studies [ 31 34 ]. In some previous studies, it was found that the superior [ 35 ] and inferior [ 34 ] sclera were significantly thinner as the degree of myopia increased, which means that the upper and lower sclera mainly stretched when the AL was elongated. For each meridian, there is a limitation in that the length is not measured between the actual scleral spurs and angle edges.…”
Section: Discussionmentioning
confidence: 99%